A Study Using Power Cycling on the Affective Responses of a Low-Volume High-Intensity Interval Training to Male Subjects with Type 2 Diabetes in Different Physical Activity Status. (28th November 2021) - Li, Jun; Jiang, Ruichen; Cheng, Wei; Ma, Haifeng
Abstract : High-intensity interval training (HIIT) has been shown in studies to enhance glucose management and cardiovascular well-being in patients with type 2 diabetes. In this study, we used power cycling to assess the physical activity levels of men with type 2 diabetes during a single low-volume HIIT session. First, fifty-six men with type 2 diabetes volunteered to take part in the study, and they were split into two groups based on the International Physical Activity Scale Short Form (IPA). To the first 1–4 labor bouts, both the sufficiently physically active and insufficiently physically active groups exhibited equal positive emotional reactions (p > 0.05 ). However, over time (about 5–10 times), both of them showed reduced emotional reactions, with a significant difference (p < 0.01 ). The insufficiently physically active group had lower mean emotional response, lowest effective response, and maximum effective response values than the sufficiently physically active group (p < 0.001 ), while the difference in RPE between the two groups was not statistically significant (p > 0.05 ). From the standpoint of emotional response, the proposed model shows that HIIT or reduced volume HIIT exercise prescriptions should be utilized with caution in physical activity programs for novices and less active and chronically sick persons. The frequency, intensity, and effects of low-volume HIIT on individuals' emotional reactions and health conditions in the T2DM group are also investigated. Furthermore, this low-volume HIIT program can be successfully applied in the real-world setting of people who are not physically active enough or who are chronically unwell.